Urgensi Pengembangan Model Konseling Kelompok Teknik Self Management Untuk Meningkatkan Kecerdasan Moral Siswa SMP - Barida, Muya; Prasetiawan, Hardi (STKIP Muhammadiyah Pringsewu, 2018)
The intelligence that must be possessed by a student is not only limited to academic achievement. Moreover, students need moral intelligence. This moral intelligence is considered the ability to control oneself in the proper direction. High-quality moral intelligence is required for students to live a personal, social life both in the family, school and community environment. This paper aims to try presenting the importance to develop a model of self-management techniques group counseling for improving moral intelligence. Through a self-management technique of group counseling model, students can improve moral intelligence outside of counseling settings so that group counseling services are more effective.Keywords: moral intelligence, self-management, group counseling.